Particulate material, method for its production and use

JP7648549B2Active Publication Date: 2025-03-18BASF SE
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2021576681
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-06-28
Filing Date
2020-06-17
Publication Date
2025-03-18
Estimated Expiration
2040-06-17

Smart Images

  • Figure 0007648549000005
    Figure 0007648549000005
  • Figure 0007648549000006
    Figure 0007648549000006
  • Figure 0007648549000007
    Figure 0007648549000007
Patent Text Reader

Abstract

Li 1+x TM 1-x O2 (In the formula, x is in the range of -0.02 to +0.05, TM is at least 93 mole % nickel and (A) at least one element M 1 (M 1 is selected from Nb, Ta, Ti, Zr, W and Mo), (B) at least one element M 2 (M 2 is selected from B, Al, Mg and Ga A particulate material of a composition represented by A particulate material having an average particle size (D50) in the range of 2 to 20 μm.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to Li 1+x TM 1-x O2 (In the formula, x is in the range of −0.02 to +0.05, TM is at least 93 mole % nickel, (A) at least one element M 1 (M 1 is selected from Nb, Ta, Ti, Zr, W and Mo; (B) at least one element M 2 (M 2 is selected from B, Al, Mg and Ga The particulate material of the composition represented by The particulate material has an average particle size (D50) in the range of 2 to 20 μm. [Background technology]

[0002] Lithiated transition metal oxides are currently used as electrode active materials in lithium-ion batteries. Extensive research and development work has been carried out in the past few years to improve properties such as charge density, specific energy, as well as other properties such as cycle life reduction and capacity loss that can adversely affect the life or applicability of lithium-ion batteries. Further efforts are being made to improve the manufacturing methods.

[0003] Many of the electrode active materials discussed today are of the lithiated nickel-cobalt-manganese oxide ("NCM material") or lithiated nickel-cobalt-aluminum oxide ("NCA material") type.

[0004] In a typical method for making cathode materials for lithium-ion batteries, a so-called precursor is first formed by co-precipitating a transition metal as a carbonate, oxide, or preferably as a hydroxide, which may or may not be basic. This precursor is then mixed with a lithium salt, such as but not limited to LiOH, Li2O, or especially Li2CO3, and calcined (combusted) at high temperature. The lithium salt(s) can be used as hydrate(s) or in dehydrated form. The calcination, or combustion, of the precursor is commonly also called thermal or heat treatment, and is usually carried out at temperatures ranging from 600 to 1,000 °C. During the thermal treatment, a solid-state reaction takes place and the electrode active material is formed. If hydroxides or carbonates are used as precursors, the solid-state reaction takes place after removal of water or carbon dioxide. The thermal treatment takes place in the heated zone of an oven or kiln. Summary of the Invention [Problem to be solved by the invention]

[0005] It has been proposed to select as high a nickel content as possible to improve the capacity of the positive electrode active material, however, it has been observed that materials such as LiNiO2 have short cycle life, significant gas evolution, and a strong increase in internal resistance during cycling, which pose major challenges for commercial applications.

[0006] Thus, there is found the particulate material defined at the outset, which is also defined below as the material of the invention or the material according to the invention. The material of the invention is explained in more detail below. [Means for solving the problem]

[0007] The material of the present invention has the formula Li 1+x TM 1-x O2, wherein x is in the range of −0.02 to +0.05, TM is at least 93 mole % nickel, (A) at least one element M 1 (M 1is selected from Nb, Ta, Ti, Zr, W and Mo; (B) at least one element M 2 (M 2 is selected from B, Al, Mg and Ga; The particulate material has an average particle size (D50) in the range of 2 to 20 μm.

[0008] This is the formula Li 1+x TM 1-x O2, where TM is (Ni 1-x1-x2 M 1 x1 M 2 x2 ) where x1>0 and x2>0 and x1+x2≦0.07. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 shows the calculation of the integral peak width second charge IPW4.1V-4.25V between 4.1V and 4.25V at the 0.2C rate of the second charge. [Diagram 2] FIG. 2 is a second cycle differential capacity plot (dQ) / (dV) of a coin-shaped half-cell containing C-CAM.1 obtained by applying the cycling procedure listed in Table 1. [Diagram 3] FIG. 3 is a second cycle differential capacity plot (dQ) / (dV) of a coin-shaped half-cell containing CAM.2 obtained by applying the cycling procedure listed in Table 1. [Figure 4] FIG. 4 is a second cycle differential capacity plot (dQ) / (dV) of a coin-type half-cell containing CAM.3 obtained by applying the cycling procedure listed in Table 1. [Diagram 5] FIG. 5 is a second cycle differential capacity plot (dQ) / (dV) of a coin-type half-cell containing CAM.4 obtained by applying the cycling procedure listed in Table 1. [Figure 6]FIG. 6 is a second cycle differential capacity plot (dQ) / (dV) of a coin-shaped half-cell containing C-CAM.5 obtained by applying the cycling procedure listed in Table 1. [Figure 7] FIG. 7 is a capacity-cycling plot of a coin-shaped half-cell containing C-CAM.1 obtained by applying the cycling procedure listed in Table 1. [Figure 8] FIG. 8 is a capacity-cycling plot of a coin-type half-cell containing CAM.2 obtained by applying the cycling procedure listed in Table 1. [Figure 9] FIG. 9 is a capacity-cycling plot of a coin-type half-cell containing CAM.3 obtained by applying the cycling procedure listed in Table 1. [Figure 10] FIG. 10 is a capacity-cycling plot of a coin-type half-cell containing CAM.4 obtained by applying the cycling procedure listed in Table 1. [Figure 11] FIG. 11 is a capacity-cycling plot of a coin-type half-cell containing the cathode active material C-CAM.5 of the present invention, obtained by applying the cycling procedure listed in Table 1. [Figure 12] FIG. 12 is a resistance-cycling plot of coin-shaped half-cells containing comparative cathode active material C-CAM.1 and inventive cathode active materials CAM.2, CAM.3, and CAM.4 obtained by applying the cycling procedure listed in Table 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The materials of the present invention are described in further detail below.

[0011] In one embodiment of the present invention, the material of the present invention is composed of spherical particles, which are particles having a spherical shape, including not only those that are exactly spherical, but also those in which the maximum and minimum diameters of at least 90% of a representative sample (number average) differ by no more than 10%.

[0012] The material of the invention has an average particle size (D50) in the range of 2 to 20 μm, preferably 5 to 16 μm. The average particle size can be determined, for example, by light scattering or LASER diffraction or electroacoustic spectroscopy. The particles are usually composed of aggregates from primary particles, and the above particle size refers to the secondary particle size.

[0013] In one embodiment of the invention, the material of the invention is composed of secondary particles which are agglomerates of primary particles. Preferably, the material of the invention is composed of spherical secondary particles which are agglomerates of primary particles. Even more preferably, the material of the invention is composed of spherical secondary particles which are agglomerates of spherical primary particles or platelets.

[0014] In one embodiment of the invention, the primary particles of the material of the invention have an average diameter in the range of 1-2000 nm, preferably 10-1000 nm, particularly preferably 50-500 nm. The average primary particle size can be determined, for example, by SEM or TEM. SEM stands for scanning electron microscopy, TEM stands for transmission electron microscopy and XRD stands for X-ray diffraction.

[0015] In one embodiment of the present invention, the material of the present invention has a thickness of 0.1 to 2.0 m. 2 / g (hereinafter also referred to as "BET surface"). The BET surface may be determined by nitrogen adsorption after outgassing the sample at 200 °C for at least 30 min according to DIN ISO 9277:2010.

[0016] TM is predominantly nickel, for example at least 93 mol %, preferably at least 95 mol %, with an upper limit of 99.5 mol % being preferred.

[0017] Some metals are ubiquitous metals such as sodium, calcium or zinc, but such trace amounts are not considered in the present description. Trace amounts in this context mean amounts of 0.05 mol % or less, relative to the total metal content TM.

[0018] TM is a compound represented by the general formula (I) (Ni a M 1 b M 2 c ) 1-d M 3 d (I) It is a combination of metals by During the ceremony, M 3 is selected from Mn and Co; a is in the range of 0.95 to 0.995, preferably 0.97 to 0.995, and more preferably 0.98 to 0.995; b is in the range of 0.002 to 0.04; c is in the range of 0.002 to 0.02, and d is in the range of 0 to 0.02; And a+b+c=1. In a preferred embodiment, b≦c.

[0019] M 1 is selected from Nb, Ta, Ti, Zr, W and Mo, and M 2 is selected from B, Al, Mg and Ga.

[0020] In one embodiment of the present invention, M 1 is Zr or Ti, and M 2 is Al.

[0021] In one embodiment of the present invention, M 1 is Ta or Nb, and M 2 is Al or B.

[0022] In one embodiment of the present invention, M 1 and M 2is homogeneously dispersed within the material of the present invention. 1 and M 2 is distributed almost homogeneously on the particles of the material of the present invention.

[0023] In one embodiment of the present invention, M 1 and M 2 At least one of these is concentrated at the grain boundaries of the particles of the material of the present invention.

[0024] In a particular embodiment of the present invention, the secondary particles of the material of the present invention are coated with a metal oxide, preferably a metal oxide that does not function as a positive electrode active material. Examples of suitable metal oxides are LiBO2, B2O3, Al2O3, Y2O3, LiAlO2, TiO2, ZrO2, Li2ZrO3, Nb2O5, LiNbO3, Ta2O5, LiTaO3.

[0025] In one embodiment of the present invention, the inventive materials have an integrated peak width of at least 25 mV in the differential capacity plot (dQ) / (dV) between 4.1 V and 4.25 V at the second charge cycle at a 0.2 C rate. Such inventive materials are particularly useful as they exhibit superior cycling stability and reduced resistance growth compared to materials having narrower peak widths.

[0026] The differential capacitance plot is typically calculated by differentiating the capacitance Q versus voltage V according to Equation 1: (dQ) / (dV)=(Q t -Q t-1 ) / (V t -V t-1 ) (Formula 1) In the formula, V t , Q t are the voltage V and capacitance Q measured at time t, and V t-1 and Q t-1are the corresponding voltage and capacitance measured at the previous time t-1. For standard C rates of 0.1-1C, data points are typically measured every 30-60 seconds or after a given voltage change (e.g., 5 mV). Data points can be further interpolated and smoothed by appropriate software to improve the quality of the (dQ) / (dV) plot.

[0027] The integrated peak width of the differential capacity (dQ) / (dV) between 4.1 V and 4.25 V at the 0.2 C rate of the second charge is the integral I of the corresponding (dQ) / (dV) plot between 4.1 V and 4.25 V in the second charge divided by the maximum m of the corresponding (dQ) / (dV) plot between 4.1 V and 4.25 V in the second charge, as shown in FIG. 1 and defined by Equation 2.

[0028] 2回目の充電 IPW 4.1V-4.25V =I / m (Equation 2)

[0029] The materials of the present invention are particularly suitable as positive electrode active materials in lithium-ion batteries. They combine good cycling stability with high energy density.

[0030] In one embodiment of the present invention, the positive electrode active material of the present invention contains Li2CO3 determined by titration in the range of 0.001 to 1% by mass with respect to the material of the present invention.

[0031] Another aspect of the invention relates to a method for producing the material of the invention, hereinafter also referred to as the method of the invention or the method according to the (present) invention. The method of the invention comprises several steps, hereinafter also referred to as step (a), step (b) etc.

[0032] Steps (a)-(e) are characterized as follows: (a) providing a particulate nickel hydroxide, nickel(II) oxide, or nickel oxyhydroxide; (b) mixing the nickel oxide / hydroxide with M 1 and M 2with a solution of one or two of the compounds of (c) optionally removing the solvent(s) from step (b); (d) adding a lithium source; (e) thermally treating the mixture resulting from step (d).

[0033] Steps (a) to (e) are described in further detail below.

[0034] In step (a), particulate nickel hydroxide, nickel oxide (II) or nickel oxyhydroxide is provided, hereinafter also collectively referred to as nickel oxide / hydroxide. In the context of the present invention, the term nickel oxyhydroxide is not limited to stoichiometric NiOOH, but to any compound of nickel having only oxide and hydroxide counterions and a maximum individual content of impurities of metals such as Mn or Mg of 2% by weight, relative to the total metal content of said nickel hydroxide, nickel oxide (II) or nickel oxyhydroxide. Preferably, the nickel hydroxide, nickel oxide (II) or nickel oxyhydroxide has a maximum total impurity content of 2% by weight, relative to the total metal content of said nickel hydroxide, nickel oxide (II) or nickel oxyhydroxide.

[0035] The nickel oxide / hydroxide provided in step (a) has an average particle size (D50) ranging from 2 to 20 μm, preferably from 4 to 16 μm. The average particle size can be determined, for example, by light scattering or LASER diffraction or electroacoustic spectroscopy. The particles may be composed of agglomerates from primary particles, and the above particle size refers to the secondary particle size.

[0036] The preferred nickel oxide / hydroxide is freshly precipitated nickel hydroxide.

[0037] In one embodiment of the present invention, the nickel oxide / hydroxide provided in step (a) has a residual water content in the range of 50 to 1,000 ppm, preferably 100 to 400 ppm. The residual water content can be determined by Karl Fischer titration.

[0038] In step (b), the nickel oxide / hydroxide is M 1 and M 2 The preferred solvents are M 1 and M 2 It depends on the type of compound.

[0039] M 1 Suitable compounds of are alkanolates or acetylacetonates of Ti, Zr, W, Ta and Nb, for example ethoxides of Ti, Zr, Nb, W and Ta, isopropoxides of Ti and Zr, acetylacetonates of Zr, Mo and / or W, mixed acetylacetonate-ethoxides of Ta. 1 The alkanolates of M are highly soluble in the corresponding alcohols. 1 Examples of water-soluble compounds include, but are not limited to, ammonium metatungstate (hydrate), ammonium orthomolybdate, ammonium heptamolybdate, ammonium dimolybdate, ammonium niobate oxalate, ammonium zirconium (IV) carbonate, either as such or as a hydrate.

[0040] M 2Suitable compounds of are Al2(SO4)3, KAl(SO4)2, and Al(NO3)3, alkanolates of Al, such as but not limited to Al(C2H5O)3, Al-tris-isopropoxide, Mg(NO3)2, Mg(SO4)2, MgC2O4, alkanolates of Mg, such as but not limited to Mg(C2H5O)2, NaBO2, H3BO3, B2O3, alkanolates of B, such as but not limited to B-tris-isopropoxide, Ga(NO3)3, Ga2(SO4)3, alkanolates of Ga, such as but not limited to Ga(CH3O)3, Ga-trisisopropoxide, or mixed salts of at least two cations, such as aluminum magnesium isopropoxide. The preferred solvent for Al2(SO4)3, KAl(SO4)2, Al(NO3)3, Mg(NO3)2, Mg(SO4)2, MgC2O4, NaBO2, H3BO3, B2O3, Ga(NO3)3, and Ga2(SO4)3 is water. 2 The alkanolates of are highly soluble in the corresponding alcohols.

[0041] In one embodiment of the present invention, M 1 and M 2 The counterions of M are the same or similar, e.g., two different alkanolate ions. In such an embodiment, the nickel oxide / hydroxide is 1 and M 2 Alternatively, the mixture may be treated with one solution containing both.

[0042] In another embodiment of the present invention, M 1 and M 2 The counter ions of are different, e.g., M 1 and the nitrate of Al. In such an embodiment, the nickel oxide / hydroxide is subsequently 1 A solution containing M 2 The emulsion is treated with a solution containing

[0043] In one embodiment of step (b), the solution used in step (b) contains 0.001 to 60% by weight of M 1 Or M 2In another embodiment of step (b), the solution used in step (b) contains a total of 0.002 to 70% by mass of M 1 and M 2 Contains the compound:

[0044] In one embodiment of the present invention, step (b) is carried out at a temperature in the range of 5 to 85°C, preferably 10 to 60°C.

[0045] In one embodiment of the present invention, step (b) is carried out at normal pressure, however, it is preferred to carry out step (b) under elevated pressure, for example at a pressure between 10 mbar and 10 bar above normal pressure, or under suction, for example at a pressure between 50 and 250 mbar below normal pressure, preferably at a pressure between 100 and 200 mbar below normal pressure.

[0046] Step (b) may be carried out, for example, in a vessel located above a filtration device and thus easily drainable. Such a vessel may be charged with the nickel oxide / hydroxide from step (a), followed by M 1 and / or M 2 In another embodiment, such a container can be charged with a solution of a compound of M 1 and / or M 2 In another embodiment, the nickel oxide / hydroxide from step (a) and the M 1 and / or M 2 The solutions of the compounds are introduced simultaneously.

[0047] In one embodiment of the present invention, the nickel oxide / hydroxide / oxyhydroxide from step (a) and M 1 and / or M 2 The volume ratio of the total solution of the above compounds is in the range of 10:1 to 1:5, preferably 10:1 to 1:1, and even more preferably 10:1 to 5:1.

[0048] M 1 and / or M 2The treatment of the nickel oxide / hydroxide with this solution may be carried out for a period of from 1 minute to 3 hours, preferably from 5 minutes to 1 hour, and even more preferably from 5 to 30 minutes.

[0049] Step (b) may be supported by a mixing operation, such as shaking, or especially by stirring or shearing (see below).

[0050] In one embodiment of the present invention, steps (b) and (c) are combined: In one embodiment of the present invention, step (b) comprises treating the nickel oxide / hydroxide from step (a) with M 1 followed by removal of the solvent by solid-liquid separation or evaporation, step (c-1), then M 2 and removing the respective solvent by solid-liquid separation techniques or evaporation, step (c-2), and drying at a maximum temperature in the range of 50-450°C.

[0051] In another embodiment of the present invention, step (b) comprises 2 followed by removal of the solvent by solid-liquid separation or evaporation; step (c-1); and then M 1 and removing the respective solvent by solid-liquid separation techniques or evaporation, step (c-2), and drying at a maximum temperature in the range of 50-450°C.

[0052] In optional step (c), the solvent(s) are removed. Suitable embodiments for the removal of the solvent are solid-liquid separation methods, such as decanting and filtration, for example on a band filter or a filter press.

[0053] In one embodiment of step (c), the slurry obtained in step (b) is discharged directly into a centrifuge, such as a decanter centrifuge or a filter centrifuge, or onto a filtration device, such as a suction filter, or onto a belt filter, preferably located directly below the vessel in which step (b) is carried out. Filtration then begins.

[0054] In a particularly preferred embodiment of the present invention, steps (b) and (c) are carried out in a stirred filter apparatus, such as a stirred pressure filter or a stirred suction filter. 1 and M 2 At most 3 minutes after combining with the solution(s) of, or immediately thereafter, begin removing the solvent by initiating filtration. At laboratory scale, steps (b) and (c) may be carried out on a Büchner funnel, and steps (b) and (c) may be supported by manual stirring.

[0055] In a preferred embodiment, step (b) is carried out in a filtration apparatus, such as a stirred filtration apparatus, which allows stirring of the slurry or filter cake in the filter. Step (c) is initiated at most 3 minutes after the start of step (b) by initiating the filtration, such as pressure filtration or suction filtration.

[0056] In one embodiment of the present invention, the solvent removal according to step (c) has a duration ranging from 1 minute to 1 hour.

[0057] In one embodiment of the invention, the stirring in steps (b), and where applicable (c), is carried out at a speed in the range of 1 to 50 revolutions per minute ("rpm"), preferably 5 to 20 rpm.

[0058] In one embodiment of the present invention, the filtration media may be selected from ceramics, sintered glass, sintered metals, organic polymer films, nonwovens, and fabrics.

[0059] In one embodiment of the present invention, steps (b) and (c) are carried out under an atmosphere with reduced CO2 and / or water content, for example with a carbon dioxide and / or water content in the range of 0.01 to 500 ppm by mass, preferably in the range of 0.1 to 50 ppm by mass. The CO2 and / or water content may be determined, for example, by optical methods using infrared light. It is even more preferred to carry out steps (b) and (c) under an atmosphere in which the carbon dioxide and / or water content is below the detection limit, for example by optical methods based on infrared light.

[0060] In one embodiment of the invention, step (c) is carried out by evaporating the solvent, preferably under reduced pressure. Such an embodiment is preferred when the solvent(s) is / are an organic solvent, such as ethanol or isopropanol.

[0061] In one embodiment of the present invention, M 1 and M 2 The solvent of the wet nickel oxide / hydroxide treated with the solution of (a) is not removed and the wet nickel oxide / hydroxide is mixed directly with the lithium source to allow for optimal distribution of lithium, step (d). This option is particularly interesting when only water is used as the solvent in step (b).

[0062] In one embodiment of the present invention, steps (b) and (c) are carried out in an atmosphere with reduced CO2 content, for example with a carbon dioxide content in the range of 0.01 to 500 ppm by mass, preferably 0.1 to 50 ppm by mass. The CO2 content may be determined, for example, by optical methods using infrared light. It is even more preferred to carry out steps (b) and (c) in an atmosphere in which the carbon dioxide content is below the detection limit, for example by using an infrared-based optical method.

[0063] In one embodiment of the invention, step (c) is carried out by evaporating the solvent, preferably under reduced pressure. Such an embodiment is preferred when the solvent(s) is / are an organic solvent, such as ethanol or isopropanol.

[0064] A powdery residue is obtained from step (c) in those embodiments in which step (c) is performed.

[0065] In step (d), a lithium source is added.

[0066] Examples of lithium sources are Li2O, LiOH and Li2CO3, each free of water or, where applicable, hydrated, e.g., LiOH·H2O. A preferred example is lithium hydroxide.

[0067] The amounts of lithium source and powdered residue are selected such that the molar ratio of Li to TM is (1+x) to 1, where x is in the range of 0.98 to 1.05.

[0068] The lithium source is preferably in the form of particles having an average diameter (D50) in the range of, for example, 3 to 10 μm, preferably 5 to 9 μm.

[0069] Examples of suitable equipment for carrying out step (d) are high shear mixers, tumbler mixers, ploughshare mixers and free fall mixers.

[0070] In one embodiment of the present invention, step (d) is carried out at a temperature ranging from ambient temperature to 200°C, preferably from 20 to 50°C.

[0071] A mixture is obtained.

[0072] Step (e) comprises subjecting said mixture to a thermal treatment. An example of step (e) is a heat treatment at a temperature in the range of 600-800° C., preferably 650-750° C. The terms "thermally treat" and "heat treatment" are used interchangeably in the context of the present invention.

[0073] In one embodiment of the present invention, the mixture resulting from step (d) is heated to 600-800° C. at a heating rate of 0.1-10° C. / min.

[0074] In one embodiment of the present invention, the temperature is increased before reaching the desired temperature of 600-800° C., preferably 650-750° C. For example, the mixture obtained from step (d) is first heated to a temperature of 350-550° C. and then held constant for a time period of 10 minutes to 4 hours, then increased to 650-800° C. and then held at 650-800° C. for 10 minutes to 10 hours.

[0075] In one embodiment of the present invention, step (e) is carried out in a roller hearth kiln, a pusher kiln or a rotary kiln, or a combination of at least two of them. Rotary kilns have the advantage of very good homogenization of the material produced therein. In roller hearth kilns and pusher kilns, different reaction conditions for different steps can be set very easily. In laboratory scale tests, box and tube furnaces and split tube furnaces are also feasible.

[0076] In one embodiment of the present invention, step (e) is carried out in an oxygen-containing atmosphere, for example in a nitrogen-air mixture, a noble gas-oxygen mixture, air, oxygen, or oxygen-enriched air. In a preferred embodiment, the atmosphere of step (d) is selected from air, oxygen, and oxygen-enriched air. The oxygen-enriched air may be, for example, a 50:50 volumetric mixture of air and oxygen. Other options are a 1:2 volumetric mixture of air and oxygen, a 1:3 volumetric mixture of air and oxygen, a 2:1 volumetric mixture of air and oxygen, and a 3:1 volumetric mixture of air and oxygen.

[0077] In one embodiment of the present invention, step (e) is carried out under a flow of gas, such as air, oxygen and oxygen-enriched air. Such a flow of gas may be defined as a forced gas flow. Such a gas flow may be a gas having the general formula Li 1+x TM 1-x 0.5-15m by O2 3 The gas flow can have a specific flow rate in the range of 10000000000000000 / h·kg of material. The volume is determined under normal conditions: 298 Kelvin and 1 atm. The gas flow is useful for the removal of gaseous cleavage products such as water and carbon dioxide.

[0078] The process of the present invention may include further steps following step (e), such as, but not limited to, an additional calcination step at a temperature in the range of 650-800°C.

[0079] In one embodiment of the present invention, step (e) has a duration ranging from 1 hour to 30 hours, preferably 10 to 24 hours. The time at temperatures above 600° C. is counted, heating and holding, while cooling time is ignored in this context.

[0080] A material that is extremely suitable as a positive electrode active material for lithium ion batteries can be obtained.

[0081] In one embodiment of the invention, the material of the invention can be treated with water and subsequently dried. In another embodiment, the particles of the material of the invention can be at least partially coated, for example, by mixing with an oxide or hydroxide, for example with aluminum hydroxide or alumina, or with boric acid, followed by a thermal treatment at 150-400° C. In another embodiment of the invention, the particles of the material of the invention can be at least partially coated by atomic layer deposition, for example, by alternating treatments (single or multiple) with trimethylaluminum and water.

[0082] A further aspect of the present invention is an electrode comprising at least one material according to the present invention. These are particularly useful in lithium-ion batteries. Lithium-ion batteries comprising at least one electrode according to the present invention show very good discharge and cycling behavior and good safety behavior.

[0083] In one embodiment of the present invention, the cathode of the present invention comprises: (A) at least one material of the invention, as described above; (B) carbon in a conductive state, and (C) binder, (D) Current collector and Includes.

[0084] In a preferred embodiment of the present invention, the cathode of the present invention comprises (A) 80 to 98% by mass of the material of the present invention; (B) 1 to 17 mass% carbon, (C) 1 to 10 mass % of a binder material and the percentages are based on the total of (A), (B) and (C).

[0085] The cathode according to the invention contains carbon, also called carbon (B) for short, in the conductive modification. Carbon (B) can be selected from soot, activated carbon, carbon nanotubes, graphene and graphite. Carbon (B) can be added directly during the preparation of the electrode material according to the invention.

[0086] The electrodes according to the invention may contain further components. They may contain a current collector (D), for example, but not limited to, an aluminum foil. They may further contain a binder material (C), also referred to below as binder (C). The current collector (D) will not be further described here.

[0087] Suitable binders (C) are preferably selected from organic (co)polymers.Suitable (co)polymers, i.e. homopolymers or copolymers, can be selected, for example, from (co)polymers obtainable by anionic, catalytic or free radical (co)polymerization, in particular from polyethylene, polyacrylonitrile, polybutadiene, polystyrene, and copolymers of at least two comonomers selected from ethylene, propylene, styrene, (meth)acrylonitrile and 1,3-butadiene.Polypropylene is also suitable.Polyisoprene and polyacrylates are furthermore suitable.Polyacrylonitrile is particularly preferred.

[0088] In the context of the present invention, polyacrylonitrile is understood to mean not only polyacrylonitrile homopolymers but also copolymers of acrylonitrile with 1,3-butadiene or with styrene. Polyacrylonitrile homopolymers are preferred.

[0089] In the context of the present invention, polyethylene refers not only to homopolyethylenes, but also to copolymerized ethylene containing at least 50 mol % of ethylene and up to 50 mol % of at least one further comonomer, such as α-olefins, such as propylene, butylene (1-butene), 1-hexene, 1-octene, 1-decene, 1-dodecene, 1-pentene, and isobutene, vinyl aromatics, such as styrene, and (meth)acrylic acid, vinyl acetate, vinyl propionate, (meth)acrylic acid, C1-C 10 -alkyl esters, in particular methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, n-butyl acrylate, 2-ethylhexyl acrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, and copolymers with maleic acid, maleic anhydride and itaconic anhydride. The polyethylene may be HDPE or LDPE.

[0090] In the context of the present invention, polypropylene is understood to mean not only homopolypropylene but also copolymers of propylene with at least 50 mol % copolymerized propylene and up to 50 mol % of at least one further comonomer, such as ethylene and an α-olefin, such as butylene, 1-hexene, 1-octene, 1-decene, 1-dodecene and 1-pentene. The polypropylene is preferably isotactic or essentially isotactic polypropylene.

[0091] In the context of the present invention, polystyrene refers not only to homopolymers of styrene, but also to C1-C4 copolymers of acrylonitrile, 1,3-butadiene, (meth)acrylic acid, and (meth)acrylic acid. 10 -alkyl esters, divinylbenzene, in particular 1,3-divinylbenzene, 1,2-diphenylethylene and α-methylstyrene copolymers are also understood to mean.

[0092] Another preferred binder (C) is polybutadiene.

[0093] Other suitable binders (C) are selected from polyethylene oxide (PEO), cellulose, carboxymethyl cellulose, polyimides and polyvinyl alcohol.

[0094] In one embodiment of the present invention, the binder (C) has an average molecular weight M in the range of 50,000 to 1,000,000 g / mol, preferably up to 500,000 g / mol. w The (co)polymers are selected from those having the formula:

[0095] The binder (C) may be a crosslinked or non-crosslinked (co)polymer.

[0096] In a particularly preferred embodiment of the present invention, the binder (C) is selected from halogenated (co)polymers, in particular fluorinated (co)polymers. Halogenated or fluorinated (co)polymers are understood to mean (co)polymers that contain at least one (co)polymerized (co)monomer with at least one halogen atom or at least one fluorine atom per molecule, more preferably at least two halogen atoms or at least two fluorine atoms per molecule. Examples include polyvinyl chloride, polyvinylidene chloride, polytetrafluoroethylene, polyvinylidene fluoride (PVdF), tetrafluoroethylene-hexafluoropropylene copolymer, vinylidene fluoride-hexafluoropropylene copolymer (PVdF-HFP), vinylidene fluoride-tetrafluoroethylene copolymer, perfluoroalkyl vinyl ether copolymer, ethylene-tetrafluoroethylene copolymer, vinylidene fluoride-chlorotrifluoroethylene copolymer and ethylene-chlorofluoroethylene copolymer.

[0097] Suitable binders (C) are especially polyvinyl alcohols and halogenated (co)polymers such as polyvinyl chloride or polyvinylidene chloride, especially fluorinated (co)polymers such as polyvinyl fluoride, especially polyvinylidene fluoride and polytetrafluoroethylene.

[0098] The electrode of the present invention may contain 3 to 10 mass % of binder(s) (d) based on the total mass of the component (a), the component (b) and carbon (c).

[0099] A further aspect of the present invention is (A) at least one cathode comprising the positive electrode active material (A) of the present invention, carbon (B), and a binder (C); (B) at least one anode; and (C) at least one electrolyte It is a battery containing

[0100] Above, the embodiment of the cathode (1) has been described in detail.

[0101] The anode (2) may contain at least one anode active material, such as carbon (graphite), TiO2, lithium titanium oxide, silicon, or tin. The anode (2) may further contain a current collector, for example a metal foil, such as copper foil.

[0102] The electrolyte (3) may include at least one non-aqueous solvent, at least one electrolyte salt, and optionally additives.

[0103] The non-aqueous solvent for the electrolyte (3) may be liquid or solid at room temperature and is preferably selected from among polymers, cyclic or acyclic ethers, cyclic and acyclic acetals and cyclic or acyclic organic carbonates.

[0104] Examples of suitable polymers include, in particular, polyalkylene glycols, preferably poly-C1-C4-alkylene glycols, and in particular polyethylene glycols. The polyethylene glycols here may contain up to 20 mol % of one or more C1-C4-alkylene glycols. The polyalkylene glycols are preferably polyalkylene glycols with two methyl or ethyl end caps.

[0105] The molecular weight M of suitable polyalkylene glycols and particularly suitable polyethylene glycols w may be at least 400 g / mol.

[0106] The molecular weight M of suitable polyalkylene glycols and particularly suitable polyethylene glycols w may be up to 5,000,000 g / mol, preferably up to 2,000,000 g / mol.

[0107] Examples of suitable acyclic ethers are, for example, diisopropyl ether, di-n-butyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, with 1,2-dimethoxyethane being preferred.

[0108] Examples of suitable cyclic ethers are tetrahydrofuran and 1,4-dioxane.

[0109] Examples of suitable acyclic acetals are, for example, dimethoxymethane, diethoxymethane, 1,1-dimethoxyethane and 1,1-diethoxyethane.

[0110] An example of a suitable cyclic acetal is 1,3-dioxane, especially 1,3-dioxolane.

[0111] Examples of suitable acyclic organic carbonates are dimethyl carbonate, ethyl methyl carbonate and diethyl carbonate.

[0112] Examples of suitable cyclic organic carbonates include those represented by the general formulas (II) and (III): [ka] (In the formula, R 1 , R 2 and R 3 can be the same or different and are selected from among hydrogen and C1-C4-alkyl, such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl and tert-butyl; R 2 and R3 and preferably neither are tert-butyl) It is a compound of the formula:

[0113] In a particularly preferred embodiment, R 1 is methyl, and R 2 and R 3 are each hydrogen or R 1 , R 2 and R 3 are hydrogen.

[0114] Another preferred cyclic organic carbonate is vinylene carbonate of formula (IV).

[0115] [ka]

[0116] The solvent(s) are preferably used in an aqueous state, ie with a water content in the range of 1 ppm to 0.1% by weight, which can be determined, for example, by Karl Fischer titration.

[0117] The electrolyte (3) further comprises at least one electrolyte salt. Suitable electrolyte salts are, in particular, lithium salts. Examples of suitable lithium salts are LiPF6, LiBF4, LiClO4, LiAsF6, LiCF3SO3, LiC(C n F 2n+1 SO2)3, LiN(C n F 2n+1 Lithium imides such as LiN(SO2F)2, Li2SiF6, LiSbF6, LiAlCl4 and the general formula (C n F 2n+1 SO2) t YLi, where m is defined as: When Y is selected from oxygen and sulfur, t=1; When Y is selected from among nitrogen and phosphorus, t=2; and When Y is selected from among carbon and silicon, t=3.

[0118] Preferred electrolyte salts are selected from LiC(CF3SO2)3, LiN(CF3SO2)2, LiPF6, LiBF4, LiClO4, with LiPF6 and LiN(CF3SO2)2 being particularly preferred.

[0119] In a preferred embodiment of the present invention, the electrolyte (3) contains at least one flame retardant. Useful flame retardants may be selected from trialkyl phosphates (wherein the alkyls are different or the same), triaryl phosphates, alkyl dialkyl phosphonates and halogenated trialkyl phosphates. Preference is given to tri-C1-C4-alkyl phosphates (wherein the C1-C4-alkyls are different or the same), tribenzyl phosphate, triphenyl phosphate, C1-C4-alkyl di-C1-C4-alkyl phosphonates and fluorinated tri-C1-C4-alkyl phosphates.

[0120] In a preferred embodiment, the electrolyte (3) comprises at least one flame retardant selected from trimethyl phosphate, CH3-P(O)(OCH3)2, triphenyl phosphate, and tris-(2,2,2-trifluoroethyl) phosphate.

[0121] The electrolyte (3) may contain 1 to 10 mass % of a flame retardant based on the total amount of the electrolyte.

[0122] In one embodiment of the invention, the battery according to the invention comprises one or more separators (4) that mechanically separate the electrodes. Suitable separators (4) are polymer films, in particular porous polymer films, that are non-reactive towards metallic lithium. Particularly suitable materials for the separators (4) are polyolefins, in particular film-forming porous polyethylene and film-forming porous polypropylene.

[0123] The separator (4) made of polyolefin, particularly polyethylene or polypropylene, can have a porosity in the range of 35 to 45%. A suitable pore size is, for example, in the range of 30 to 500 nm.

[0124] In another embodiment of the present invention, the separator (4) can be selected from PET nonwovens filled with inorganic particles. Such separators can have a porosity in the range of 40-55%. Suitable pore sizes are, for example, in the range of 80-750 nm.

[0125] The battery according to the invention may further comprise a housing which may have any shape, for example that of a rectangular parallelepiped or a cylindrical disk. In one variant, a metal foil configured as a pouch is used as the housing.

[0126] The battery according to the invention offers very good discharge and cycling behaviour, especially with regard to capacity loss, especially at high temperatures (above 45° C., for example up to 60° C.).

[0127] The battery according to the invention may comprise two or more electrochemical cells, which may be combined with each other, for example connected in series or in parallel. A series connection is preferred. In the battery according to the invention, at least one of the electrochemical cells contains at least one electrode according to the invention. Preferably, in the electrochemical cell according to the invention, the majority of the electrochemical cells contain the electrode according to the invention. Even more preferably, in the battery according to the invention, all the electrochemical cells contain the electrode according to the invention.

[0128] The present invention further provides the use of the battery according to the invention in equipment, in particular mobile equipment. Examples of mobile equipment are vehicles, such as automobiles, bicycles, aircraft, or water vehicles, such as boats or ships. Other examples of mobile equipment are manually operated, such as computers, in particular laptops, phones, or powered hand tools, for example in the construction sector, in particular drills, battery-powered screwdrivers, or battery-powered staplers. EXAMPLES

[0129] The present invention will now be further illustrated by examples.

[0130] The average particle size (D50) was determined by dynamic light scattering ("DLS"). Percentages are by weight unless otherwise stated.

[0131] Step (a.1): A nickel sulfate aqueous solution (1.65 mol / kg solution) and a 25 wt.% NaOH aqueous solution were combined, using ammonia as a complexing agent, to obtain a spherical Ni(OH)2 precursor. The pH value was set to 12.6. The freshly precipitated Ni(OH)2 was washed with water, sieved, and dried at 120 °C for 12 h. The freshly precipitated Ni(OH)2 was then poured into an alumina crucible and dried in a furnace under oxygen atmosphere (10 exchanges / h) at 500 °C for 3 h with a heating rate of 3 °C / min and a cooling rate of 10 °C / min to obtain the precursor p-CAM.1. p-CAM.1 was NiO with a D50 of 6 μm.

[0132] Preparation of Comparative Positive Electrode Active Material C-CAM.1: The dehydrated precursor p-CAM.1 was mixed with LiOH·H2O in a molar ratio of Li:Ni of 1.01:1, poured into an alumina crucible, and heated at 350 °C for 4 h and 700 °C for 6 h under oxygen atmosphere (10 exchanges / h) using a heating rate of 3 °C / min. The resulting material was cooled to ambient temperature at a cooling rate of 10 °C / min and subsequently sieved using a mesh size of 30 μm to obtain the comparative material C-CAM.1 with a D50 of 6 μm.

[0133] Preparation of the material CAM.2 according to the invention: Step (b.1.2): 100 g of precursor p-CAM.1 was placed in a beaker. 0.98 g of Al(NO3)3 nonahydrate and 0.32 g of boric acid H3BO3 were dissolved in 35 ml of deionized water. The resulting solution was added dropwise to the beaker via a dropping funnel at ambient temperature over a period of 5 min until the precursor was immersed in the liquid. No visible liquid film formed on the precursor p-CAM.1. The resulting slurry was stirred in the beaker for 30 min. The individual amounts of Al, B and Ni were set to ensure a molar Ni:Al ratio of 0.991:0.002 and a molar Ni:B ratio of 0.991:0.004.

[0134] Step (c.1.2): The mixture was then heated at 120° C. under vacuum for 6 hours to remove water, yielding p-CAM.2.1.

[0135] Step (b.2.2): The p-CAM.2.1 obtained from step (c.1.2) was placed in a beaker. 1.24 g of niobium (V) ethoxide was dissolved in 28 ml of dry ethanol. The resulting solution was added dropwise to the beaker via a dropping funnel at ambient temperature over a period of 5 minutes until the precursor was immersed in the liquid. No visible liquid film formed on top of the precursor p-CAM.2.1. The resulting slurry was stirred in the beaker for 30 minutes. Step (b.2.2) was carried out under a nitrogen atmosphere. The individual amounts of Nb and Ni were set to ensure a molar Ni:Nb ratio of 0.991:0.003.

[0136] Step (c.2.2): The slurry was then heated under vacuum at 120° C. for 6 hours to remove ethanol, yielding p-CAM.2.2.

[0137] Steps (d.1.2) and (e.1.2): The precursor p-CAM.2.2 was mixed with LiOH·H2O in a molar ratio of Li:(Ni+Nb+B+Al) of 1.01:1, poured into an alumina crucible and heated at 350°C for 4 hours and 700°C for 6 hours under oxygen atmosphere (10 exchanges / hour) with a heating rate of 3°C / min and a cooling rate of 10°C / min. The material so obtained was then sieved using a mesh size of 30 μm to obtain the cathode active material CAM.2 of the present invention.

[0138] D50: 6μm.

[0139] Preparation of the material CAM.3 according to the invention: Step (b.1.3): 100 g of precursor p-CAM.1 was placed in a beaker. 1.80 g of Ga(NO3)3 nitrate and 0.52 g of ammonium heptamolybdate, (NH4)6Mo7O 24 was dissolved in 35 ml of deionized water. The resulting solution was added dropwise via a dropping funnel at ambient temperature over a period of 5 minutes to a beaker until the precursor was immersed in the liquid. No visible liquid film formed on the precursor p-CAM.1. The resulting slurry was stirred in the beaker for 30 minutes. The individual amounts of Ga, Mo and Ni were set to ensure a molar Ni:Mo ratio of 0.991:0.002 and a molar Ni:Ga ratio of 0.991:0.004.

[0140] Step (c.1.3): The slurry was then heated under vacuum at 120° C. for 6 hours to remove water to obtain p-CAM.3.1.

[0141] Step (b.2.3): The p-CAM.3.1 obtained from step (c.1.3) was placed in a beaker. 1.60 g of tantalum(V) ethoxide was dissolved in 28 ml of dry ethanol. The resulting solution was added dropwise to the beaker via a dropping funnel at ambient temperature over a period of 5 minutes until the precursor was immersed in the liquid. No visible liquid film was formed on top of the precursor p-CAM.3.1. The resulting slurry was stirred in the beaker for 30 minutes. Step (b.2.3) was carried out under a nitrogen atmosphere. The individual amounts of Ta and Ni were set to ensure a molar Ni:Ta ratio of 0.991:0.003.

[0142] Step (c.2.3): The slurry was then heated under vacuum at 120° C. for 6 hours to remove ethanol, yielding impregnated p-CAM.3.2.

[0143] Steps (d.3) and (e.3): The precursor p-CAM.3.2 was mixed with LiOH·H2O in a molar ratio of Li:(Ni+Ta+Ga+Mo) of 1.01:1, poured into an alumina crucible and heated at 350°C for 4 h and 700°C for 6 h under oxygen atmosphere (10 exchanges / h) with a heating rate of 3°C / min and a cooling rate of 10°C / min. The material so obtained was then sieved using a mesh size of 30 μm to obtain the inventive CAM.3 with a D50 of 6 μm.

[0144] Preparation of the material CAM.4 according to the invention: Step (b.1.4) and Step (c.1.4): 0.68 g of magnesium nitrate and 3.22 g of ammonium zirconium (IV) carbonate were dissolved in 100 ml of deionized water. The solution was placed in a dropping funnel and added dropwise over a period of 5 minutes at ambient temperature to an amount of 100 g of precursor p-CAM.1 placed in a beaker until the precursor was immersed in the liquid but before a visible liquid film formed on the precursor p-CAM.1. During this procedure, the precursor p-CAM.1 was stirred in the beaker for 30 minutes. The water was then removed by heating the slurry at 120° C. under vacuum for 6 hours. The remaining solution of magnesium and zirconium was added to the dried pCAM under the same conditions as above until the precursor was again completely immersed in the liquid but before a visible liquid film formed. The mixture was then again heated at 120° C. under vacuum for 6 hours to remove the water. This procedure was repeated until all the solution of zirconium and magnesium was consumed. After a final drying at 120° C. for 6 hours, p-CAM.4.1 was obtained. The amounts of Mg, Zr and Ni were set to ensure a Ni:Mg molar ratio of 0.991:0.002 and a Ni:Zr molar ratio of 0.991:0.004.

[0145] Step (b.2.4): The p-CAM.4.1 obtained from step (c.1.4) was placed in a beaker. 1.12 g of titanium(IV)-isopropoxide was dissolved in 28 ml of dry ethanol. The resulting solution was added dropwise to the beaker via a dropping funnel at ambient temperature over a period of 5 minutes until the precursor was immersed in the liquid. No visible liquid film formed on the precursor p-CAM.4.1. The resulting slurry was stirred in the beaker for 30 minutes. Step (b.2.4) was carried out entirely under a nitrogen atmosphere. The individual amounts of Ti and Ni were set to ensure a molar Ni:Ti ratio of 0.991:0.003.

[0146] Step (c.2.4): Subsequently, the ethanol was removed by heating the mixture at 120° C. under vacuum for 6 hours to obtain the impregnated p-CAM.4.2.

[0147] Steps (d.4) and (e.4): The precursor p-CAM.4.2 was mixed with LiOH·H2O in a molar ratio of Li:(Ni+Mg+Ti+Zr) of 1.01:1, poured into an alumina crucible and heated at 350°C for 4 h and 700°C for 6 h under oxygen atmosphere (10 exchanges / h) with a heating rate of 3°C / min and a cooling rate of 10°C / min. The material so obtained was then sieved using a mesh size of 30 μm to obtain the inventive CAM.4 with a D50 of 6 μm.

[0148] Preparation of Comparative Positive Electrode Active Material C-CAM.5: Step C-(b.1.5): 100 g of precursor p-CAM.1 was placed in a beaker. 6.54 g of cobalt(II) nitrate was dissolved in 35 ml of deionized water. The resulting solution was added dropwise to the beaker via a dropping funnel at ambient temperature over a period of 5 min until the precursor was immersed in the liquid. No visible liquid film formed on top of the precursor. The resulting slurry was stirred in the beaker for 30 min. The respective amounts of Co and Ni were set to ensure a Ni:Co molar ratio of 0.98:0.02.

[0149] Step C-(c.1.5): The mixture was then heated at 120° C. under vacuum for 6 hours to remove water, yielding comparative precursor p-CAM.5.

[0150] Step C-(d.1.5) and (e.1.5): Comparative precursor Cp-CAM.5 was mixed with LiOH·H2O in a molar ratio of Li:(Ni+Co) of 1.01:1, poured into an alumina crucible and heated at 350°C for 4 h and 700°C for 6 h under oxygen atmosphere (10 exchanges / h) with a heating rate of 3°C / min and a cooling rate of 10°C / min. The material so obtained was then sieved using a mesh size of 30 μm to obtain comparative cathode active material C-CAM.5 with a D50 of 6 μm.

[0151] Electrode fabrication: The electrodes contained 94% CAM, 3% carbon black (Super C65) and 3% binder (polyvinylidene fluoride, Solef5130). The slurry was mixed in N-methyl-2-pyrrolidone and cast onto aluminum foil by doctor blade. The electrodes were dried in vacuum at 105°C for 6 hours, after which circular electrodes were punched out, weighed and dried under vacuum at 120°C for 12 hours before being placed in an Ar-filled glove box.

[0152] Half-cell electrochemical measurements: A coin-shaped electrochemical cell was assembled in an argon-filled glove box. A 14 mm diameter positive (loading 8.0 ± 0.5 mg cm) -2 The ) electrodes were separated from the 0.58 thick Li foil by a glass fiber separator (Whatman GF / D). A volume of 95 μl of 1 M LiPF6 in ethylene carbonate (EC):ethyl methyl carbonate (EMC) 3:7 by mass was used as the electrolyte. The cells were galvanostatically cycled in a Maccor 4000 battery cycler between 3.1 V and 4.3 V at room temperature by applying the following C-rates until 70% of the initial discharge capacity was reached at the specific discharge step:

[0153] [Table 1]

[0154] After charging at the listed C-rates, all charging steps except the first were followed by a 1-hour constant voltage step (CV * ) or before the current reached 0.02C.

[0155] During cycling, data points were collected every minute or after a voltage change of at least 5 mV occurred. Four electrochemical cells were assembled for each material, and the corresponding cycling profiles, capacity and resistance were obtained by averaging the four cells.

[0156] During the resistance measurements (performed every 25 cycles at 25°C), the cells were charged at 0.2C to a state of charge of 50% of the previous discharge capacity. A 30 min open circuit step followed to equilibrate the cells. Finally, a discharge current of 2.5C was applied for 30 s and the resistance was measured. At the end of the current pulse, the cells were again equilibrated at open circuit for 30 min and further discharged at 0.2C to 3.0 V.

[0157] To calculate the resistance, the voltage before the application of the 2.5C pulse current, V0s, and the voltage 30 seconds after the application of the 2.5C pulse current, V30s, and the 2.5C current value (j in A) were obtained. The resistance was calculated using Equation 3 (V: voltage, j: 2.5C pulse current).

[0158] R=(V0s-V30s) / j (Formula 3)

[0159] [Table 2]

Claims

1. Composition formula Li 1+x TM 1-x O 2 (In the formula, x is in the range of −0.02 to +0.05; TM is a compound represented by the general formula (I) (Ni a M 1 b M 2 c ) 1-d M 3 d (I) (In the formula, M 1 is Zr or Ti and M 2 is Mg, or M 1 is Ta or Nb and M 2 is Al or B; or M 1 is Mo or Ta, and M 2 is Ga; M 3 is selected from Mn and Co; a is in the range of 0.95 to 0.995; b is in the range of 0.002 to 0.04; c is in the range of 0.002 to 0.02, and d is in the range of 0 to 0.02; a + b + c = 1) (The metal combination represented by A particulate material represented by the formula: A particulate material having an average particle size (D50) in the range of 2 to 20 μm.

2. 2. The particulate material of claim 1, wherein d is 0.

3. The material has an integrated peak width of at least 25 mV in a differential capacity plot (dQ) / (dV) between 4.1 V and 4.25 V at a 0.2 C rate during the second charge cycle. 2回目の充電 IPW 4.1V-4.25V 3. The particulate material according to claim 1 or 2, having the following structure:

4. 4. A particulate material according to any one of claims 1 to 3, wherein b≦c.

5. A method for producing a particulate material according to any one of claims 1 to 4, comprising the steps of: (a) providing a particulate nickel hydroxide, nickel(II) oxide, or nickel oxyhydroxide; (b) treating the nickel oxide / hydroxide or nickel oxyhydroxide with M 1 and M. 2 with a solution of one or two of the compounds of (c) optionally removing said solvent(s) from step (b); (d) adding a lithium source; (e) thermally treating the mixture resulting from step (d). The method includes:

6. The method of claim 5, wherein step (e) is carried out at a maximum temperature in the range of 650 to 750°C.

7. 7. The process according to claim 5 or 6, wherein step (c) is carried out by a solid-liquid separation process.

Citation Information

Patent Citations

  • High-nickel and low-cobalt ternary cathode material and preparation method thereof

    CN108767239A

  • Nonaqueous electrolyte secondary battery

    JP1996213052A

  • Method for producing nickel lithium metal composite oxide

    JP2017193471A

  • Positive electrode active material, method for producing the same, and lithium secondary battery including a positive electrode containing the same

    JP2022520866A

  • Method for diagnosing deterioration of electrode active material for lithium secondary battery

    JP2023500548A